OSTEOPROTEGERIN, RANK, RANKL - Stejskal, David; Bartek, Josef; Pastorkova, Radmila; Ruzicka, Viktor; Oral, Ivo; Horalik, Dalimil (Biomedical papers, 2001)
Osteoprotegerin, RANK (Receptor Activator of Nuclear factor kappa B) and RANKL (Receptor Activator ofNuclear faktor kappa B ligand) became the aim of intensive researche. RANK is considered as a hematopoieticsurface receptor controling osteoclastogenesis and calcium metabolism. RANKL may promote osteoresorption byinduction of cathepsin K gene expression. The present paper summarizes the most significant data in osteoprotegerin,RANK and RANKL problems obtained.
Keywords: Osteoprotegerin / RANK / RANKL